First data on the age and growth of Brazilian flathead Percophis brasiliensis (Pisces: Perciformes) in San Matías Gulf, northern Patagonia (Argentina) - López, María Eugenia (2019)
Brazilian flathead Percophis brasiliensis is a commercially important perciform fish caught as bycatch by trawlers throughout its latitudinal distribution range (from 23° S in Brazil to 47° S in Argentina). It is associated with the catches of Argentine hake Merluccius hubbsi and Patagonian red shrimp Pleocticus muelleri in San Matías Gulf (SMG). The main objective of this study was to describe the first data on the growth of this species in SMG and to compare the results with available information for other areas of the Argentine Continental Shelf (ACS). The study was carried out using 294 specimens (196 females, 97 males and one of indeterminate sex) collected over four non-consecutive years from commercial/recreational fishing and during research cruises. The age of individuals was determined by reading and counting opaque-hyaline rings on the sagittae otoliths. The maximum ages observed were 14 years for females and 12 years for males. Growth parameters were estimated using the von Bertalanffy mode. Significant differences in L∞ parameter between sexes were found (L∞ males = 54.58 cm; L∞ females = 78.31 cm, p < 0.05). Growth parameters were different from those determined in previous studies for the ACS.